KEBIJAKAN PENDIDIKAN KOSMOPOLITAN MUHAMMADIYAH DI TENGAH TANTANGAN ERA DISRUPSI - Bakhtiar, Sony (Department of Social Science, Faculty of Social Science &Law, Universitas Negeri Surabaya, 2019)
At present, in the era of disruption of advances in information technology began to replace the role of humans in several fields of work.This situation will increase the number of unemployed if there is no anticipation.Senior High School Jember Muhammadiyahseeks to provide balanced attention between intracurricular and extracurricular programs. Extracurricular activities can hone the potential of students' interests and talents. Extracurricular provides added value in the form of scientific, creative and innovative thinking. This is the core of edupreneurship in high school in the face of the era of disruption. The application of edupreneurship requires the commitment of the principal and the teacher. This study aims to determine the application of edupreneurship in intracurricular and extracurricular activities during 2016-2018 at Muhammadiyah 3 Jember High School. The method of this research is a mixed descriptive method with data collection techniques through interviews, direct observation in the field and literature studies. The results of this study indicate that some teachers and students are able to produce original, creative and innovative work based problems through intracurricular and extracurricular. Students also understand more by teachers who are able to connect theory with subjects through sources of Islamic teachings and human values.